2023
DOI: 10.26434/chemrxiv-2023-s8j30
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photocatalyzed [3sigma + 2sigma] and [3sigma + 2pi] cycloadditions for the synthesis of bicyclo[3.1.1]heptanes and cyclopentenes.

Abstract: We report the use of photocatalysis for the homolytic ring-opening of carbonyl cyclopropanes. In contrast to previous studies, our approach does not require a metal co-catalyst or a strong reductant. The carbonyl cyclopropanes can be em-ployed for both [3sigma + 2sigma] and [3sigma + 2pi] cycloaddition with either bicyclo[1.1.0]butanes and alkenes, yielding bicy-clo[3.1.1]heptanes and cyclopentanes respectively. Bicyclo[3.1.1]heptane (BCHs) have been recently highlighted as bi-oisosteres for meta-substituted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The design of mimics of meta -substituted arenes has been much less well-explored than the para - and ortho -topologies, but recent developments suggest that this circumstance may be on the cusp of change. Early studies had probed oximes (Figure E) for their potential to act as topologically chameleonic mimics of meta -substituted arenes in the context of adrenergic ligands. , The potential for a 1,2-disubstitued BCP ring system to mimic a meta -substituted arene has been examined in the context of the cystic fibrosis transmembrane regulator (CFTR) chaperone lumacaftor ( 195 ), but this was not a productive molecule edit since the (+)-enantiomer of 196 was 70-fold less potent and the (−)-isomer not appreciably active at a concentration of 30 μM . Solubility at pH = 7 was similar for all three compounds, but 196 offered 40-fold enhanced solubility at the more acidic pH = 2.…”
Section: Bioisosteres Of Phenyl Ringsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of mimics of meta -substituted arenes has been much less well-explored than the para - and ortho -topologies, but recent developments suggest that this circumstance may be on the cusp of change. Early studies had probed oximes (Figure E) for their potential to act as topologically chameleonic mimics of meta -substituted arenes in the context of adrenergic ligands. , The potential for a 1,2-disubstitued BCP ring system to mimic a meta -substituted arene has been examined in the context of the cystic fibrosis transmembrane regulator (CFTR) chaperone lumacaftor ( 195 ), but this was not a productive molecule edit since the (+)-enantiomer of 196 was 70-fold less potent and the (−)-isomer not appreciably active at a concentration of 30 μM . Solubility at pH = 7 was similar for all three compounds, but 196 offered 40-fold enhanced solubility at the more acidic pH = 2.…”
Section: Bioisosteres Of Phenyl Ringsmentioning
confidence: 99%
“…The insertion of two carbon atoms into one of the bridges of the BCP ring affords a bicyclo[3.1.1]­heptane (BCHep) ring system that is a cyclohexane ring with a one carbon atom bridge installed between the 1- and 3-positions, a geometry that will largely preserve the 120° exit vectors of a meta -substituted benzene (Figure B). , The design principle builds on observations from an analysis of a large number of MMPs that revealed that a cyclohexane moiety acts as an effective replacement for a phenyl ring in a wide range of biochemical pharmacological settings about 50% of the time . However, replacement of a phenyl ring with a cyclohexane increases the Log P value by ∼0.5 units.…”
Section: Bioisosteres Of Phenyl Ringsmentioning
confidence: 99%
“…9,36 The oxa-BCH unit is further claimed to be 30 times more hydrophilic, less lipophilic, and more stable than the corresponding parent meta-substituted benzene ring. Since the conceptual advancement of "escape from flatland", many reports from Brown, 3 Studer, 10 Procter, 11 Molander, 12 Leitch, 13 Aggarwal, 14 Li, 15 Wang, 16 Waser, 17 Shi, 18 Bach, 19 and our group 5,20 displayed BCBs as potential precursors for 3D-chemical space exploration.…”
Section: ■ Introductionmentioning
confidence: 98%
“…2 They can be used as either photoactive substrates 2 or as photocatalysts as exemplified by thioxanthone 3a or benzophenone. 3b,c The excitation of carbonyl compounds can be achieved via either energy transfer catalysis [4][5][6][7][8] or direct excitation (Scheme 1A). 2 Although energy transfer catalysis provides milder conditions to activate molecules with a low-energy light source, extensive optimization of the photocatalyst is usually required.…”
Section: Introductionmentioning
confidence: 99%